Determinance Of Waste Management In Construction - Ningrum, Dhea Agusty; Rasyid, MHD. Andi; Siagian, Tomy Sun; OK, Ulfa Khairani (UNIVERSITAS PAKUAN, 2024)
The purpose of this research is to analyze the determinants of construction waste management to support the achievement of Green Construction. This is based on the construction industry's activities becoming one of the main contributors to negative environmental impacts. The type of research used in this study is the descriptive quantitative research method. The population in this study is construction management companies operating in Indonesia. The sample was taken using the random sampling method with a total of 100 construction projects.The data analysis techniques used in this research are descriptive analysis and variance-based Structural Equation Modeling analysis. The research results show that sustainable development, which is an elaboration of the green construction concept, through the implementation of a waste management system, contributes to the creation of a good environment through aspects such as: Storage Handling; Reuse Material; Human Resource Competence; Field Implementation; and Work Methods. From the analysis conducted, these five aspects have a significant impact in minimizing material waste from construction activities.